2018
DOI: 10.1002/hed.25439
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of primary parapharyngeal space tumors

Abstract: The parapharyngeal space is a complex anatomical area. Primary parapharyngeal tumors are rare tumors and 80% of them are benign. A variety of tumor types can develop in this location; most common are salivary gland neoplasm and neurogenic tumors. The management of these tumors has improved greatly owing to the developments in imaging techniques, surgery, and radiotherapy. Most tumors can be removed with a low rate of complications and recurrence. The transcervical approach is the most frequently used. In some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 96 publications
1
84
0
Order By: Relevance
“…4,8,9 A patient's suitability for surgery can be determined according to tumor type, width, and relation to vital anatomic structures. 9 Various approaches have been described to reach the PPS. 10 In tumor resection, all approaches can be performed alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8,9 A patient's suitability for surgery can be determined according to tumor type, width, and relation to vital anatomic structures. 9 Various approaches have been described to reach the PPS. 10 In tumor resection, all approaches can be performed alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…13 In some studies in the literature, the transcervical approach was the most common surgical approach to PPS tumors. 9 Riffat et al…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Satisfactory outcomes have been reported following the adoption of minimally invasive techniques for the resection of benign tumors located in both the ITF and PPS. 5,6 The PPS is traditionally divided into the prestyloid and retro-styloid compartments by the styloid process and the stylopharyngeal aponeurosis. 4,7 The prestyloid PPS mainly comprises adipose tissue, minor salivary glands, lymph node, and the deep lobe of the parotid gland.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence of pleomorphic adenoma are frequently reported. 6 However, reports of BSA in PPS are sparse. 14 During a retrospective analysis of patients with benign tumors of the PPS resected via an endoscopic transoral corridor, we identified that four patients with a histopathological diagnosis of BSA.…”
Section: Introductionmentioning
confidence: 99%
“…The parapharyngeal space is a pyramidshaped space located between the base of the skull and the hyoid bone, lateral to the naso-oropharynx and medial to the jaw [1,2]. It contains the deep lobe of the parotid gland, cranial nerves IX -XII, the internal jugular vein, and the carotid artery [1]. A variety of benign and malignant tumors arise in the parapharyngeal space, the most common being of salivary gland and neurogenic origin [1].…”
mentioning
confidence: 99%